1969
DOI: 10.1113/jphysiol.1969.sp008917
|View full text |Cite
|
Sign up to set email alerts
|

Identification of adenosine triphosphate in human plasma and the concentration in the venous effluent of forearm muscles before, during and after sustained contractions

Abstract: SUMMARY1. When diluted human plasma is perfused through a frog heart, a marked augmentation of the heartbeat is produced which is very similar in action to that of low concentrations of adenosine triphosphate (ATP) on the heart. 2. It was established that the substance in the plasma responsible for the heart stimulation was ATP. The following tests were used: (a) the diluted plasma emitted light from firefly lantern extract characteristic of the light signal produced by a solution of ATP; (b) the stimulatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 11 publications
7
67
0
Order By: Relevance
“…2011). During exercise in normal environmental conditions, plasma ATP also increases in the forearm and leg circulations (Forrester & Lind, 1969; Forrester, 1972; González‐Alonso et al . 2002; Mortensen et al .…”
Section: Introductionmentioning
confidence: 99%
“…2011). During exercise in normal environmental conditions, plasma ATP also increases in the forearm and leg circulations (Forrester & Lind, 1969; Forrester, 1972; González‐Alonso et al . 2002; Mortensen et al .…”
Section: Introductionmentioning
confidence: 99%
“…First, since indomethacin inhibits prostaglandin synthetase (Ferreira, Moncada & Vane, 1971;Vane, 1971) the results could be ascribed to supersensitivity; secondly, indomethacin inhibits prostaglandin dehydrogenase in the dose-range used (Flower, 1974), so retarded break-down of PGE1 was feasible. been detected in vasoactive quantities in the venous effluent from exercising human forearm muscle (Forrester & Lind, 1969;Forrester, 1972) and has recently been identified in the blood stream after whole-body exercise (Parkinson, 1973).…”
Section: Pmentioning
confidence: 99%
“…This protection from ischemic insult was suggested to occur through inhibition of ATP release from Panx1 channels, by a negative feedback mechanism involving the P2X 7 purinergic receptor [156]. Prolonged activation of P2X 7 receptors results in the opening of a large pore permeable to divalent cations such as Ca 2+ that eventually leads to cell death [170][171][172]. This study revealed that ischemic insult to cultured cortical astrocytes resulted in initial ATP release from Panx1 channels that in turn activated P2X 7 receptors, inducing closure of Panx1 channels, which prevented loss of integral intracellular constituents and averted cell death.…”
Section: Pannexin Channelsmentioning
confidence: 99%
“…The effects of ATP signaling have been observed throughout the vasculature in both homeostatic and pathological conditions, including: reactive hyperemia [7,8], hypoxiainduced vasodilation [9,10], alpha-adrenergic receptor mediated vasoconstriction [11], hypertension [12], VSMC proliferation in atherosclerosis and vascular inflammation [13][14][15][16][17]. Elucidation of the mechanisms regulating purine nucleotide release in the cells comprising the vascular wall is critical for both understanding the pathogenesis of vascular diseases and the identification of novel drug interventions.…”
Section: Purinergic Signaling In the Vasculaturementioning
confidence: 99%
See 1 more Smart Citation